Organ dose measurement using Optically Stimulated Luminescence Detector (OSLD) during CT examination. (October 2017) - Yusuf, Muhammad; Alothmany, Nazeeh; Abdulrahman Kinsara, Abdulraheem
Abstract: This study provides detailed information regarding the imaging doses to patient radiosensitive organs from a kilovoltage computed tomography (CT) scan procedure using OSLD. The study reports discrepancies between the measured dose and the calculated dose from the ImPACT scan, as well as a comparison with the dose from a chest X-ray radiography procedure. OSLDs were inserted in several organs, including the brain, eyes, thyroid, lung, heart, spinal cord, breast, spleen, stomach, liver and ovaries, of the RANDO phantom. Standard clinical scanning protocols were used for each individual site, including the brain, thyroid, lung, breast, stomach, liver and ovaries. The measured absorbed doses were then compared with the simulated dose obtained from the ImPACT scan. Additionally, the equivalent doses for each organ were calculated and compared with the dose from a chest X-ray radiography procedure. Absorbed organ doses measured by OSLD in the RANDO phantom of up to 17 mGy depend on the organ scanned and the scanning protocols used. A maximum 9.82% difference was observed between the target organ dose measured by OSLD and the results from the ImPACT scan. The maximum equivalent organ dose measured during this experiment was equal to 99.899 times the equivalent dose from a chest X-ray radiography procedure. The discrepancies between the measured dose with the OSLD and the calculated dose from the ImPACT scan were within 10%. This report recommends the use of OSLD for measuring the absorbed organ dose during CT examination. Highlights: The use of OSLD in organ dose measurement during CT examination is proposed. Radiation dose is measured independently in various organs during typical scans. Maximum 10% difference between the OSLD measurements and ImPACT scan calculation. Equivalent organ dose measured is maximum 99.899 times to a chest X-ray radiography. OSLD can be used as an alternative tool for measuring organ dose in CT examination.